Sleep problems of healthcare workers in tertiary hospital and influencing factors identified through a multilevel analysis: a cross-sectional study in China. Issue 12 (29th December 2019) - Liu, Huan; Liu, Jingjing; Chen, Mingxi; Tan, Xiao; Zheng, Tong; Kang, Zheng; Gao, Lijun; Jiao, Mingli; Ning, Ning; Liang, Libo; Wu, Qunhong; Hao, Yanhua
Abstract : Objectives: Sleep problems are common among healthcare workers, especially among those who work in tertiary hospitals; however, studies focusing on healthcare workers in tertiary hospitals in China are limited. Therefore, we aimed to examine the prevalence of sleep problems among tertiary hospital employees in China and identify associated factors. Design: Cross-sectional questionnaire survey study. Setting: The study was conducted in 317 departments at 33 tertiary hospitals in the Heilongjiang Province, China. Participants: The study included a representative sample of 4007 healthcare workers, including clinicians, medical technicians and office workers, who were selected using a multistage cluster sampling method. Ultimately, 3810 participants completed valid questionnaires, yielding a response rate of 95%. Primary and secondary outcome measures: Participants completed a structured questionnaire which collected data regarding demographics, sleep problems, employment, chronic pain and health-related behaviours. A two-level logistic regression model was constructed to examine determinants of sleep problems. Results: We found that nearly half of the respondents reported experiencing sleep problems. The two-level logistic model suggested a positive association of sleep problems with headache (OR=2.64, 95% CI=2.27 to 3.07), working hours (OR=1.41, 95% CI=1.20 to 1.66) and night shifts (OR=1.43, 95% CI=1.21 to 1.69). In contrast, regular diet (OR=0.44, 95% CI=0.36 to 0.53) and exercise (OR=0.65, 95% CI=0.53 to 0.80) protected the study population against sleep problems. Conclusions: We found that sleep problems are prominent among tertiary hospital employees in China. The risk factor most strongly associated with sleep problems was headaches. To alleviate sleep problems in this population, medical institutions and health policy makers should establish reasonable working schedules and night-shift work systems, while the healthcare workers themselves should pay attention to their chronic pain problems and engage in regular diet and exercise.